Hemispheric lateralization of singing after intracarotid sodium amylobarbitone - Gordon, H. W. (1974)
Hemispheric lateralization of singing was investigated in patients who had transient hemiplegia after intracarotid injection of sodium amylobarbitone. It was found that after right carotid injection singing was markedly deficient, whereas speech remained relatively intact. Songs were sung in a monotone, devoid of correct pitch rendering; rhythm was much less affected. By contrast, singing was less disturbed than speech after left carotid injection. The observations indicated a double dissociation; the right hemisphere contributed more for singing, whereas the left demonstrated its usual dominance for speech. A model is proposed that encompasses audible stimuli as well as tactual or visual into a scheme of functional lateralization wherein the right hemisphere specializes in processing a complete, time-independent stimulus configuration and the left in a series of successive, time-dependent units.